Mixing Plate and Beam Elements in FEAP: A Plate Stiffened with Beams - Limkatanyu, Suchart (Engineering and Applied Science Research, 2013)
This paper investigates the mixability of plate and beam elcments in finite element meshes and is separated into three parts. The first part is a look at verifying if plate and beam elements could be intermixed in a general-purpose finite element program like FEAP in this study. The second part is a look at how well a finite element model of a simple plate with edge beams (using both shell and beam elements) could match the available analytical solutions. The third part investigates the similarities and differences encountered when modeling the plate with edge beams using either beam elements or shell elements to represent the beam-stiffeners. The model assessments are conducted both under static and dynamic analysis. The results indicate that FEAP haridles the problem of mixing beam and platc elements combinations, hence allowing both modeling and analyzing much faster as long as one pays attentions to the torsional characteristies of the beam profile